A Frames analysis of radiation therapy program director leadership. - Turley CL (Radiation Therapist)
This study examined radiation therapy program directors' leadership approaches using frames theory. Results indicated that 73% of program directors consistently used the human resource frame, 70% the structural frame, 41% the symbolic frame and only 32% the political frame. Fewer than half of respondents (44%) demonstrated multiframe leadership. Because effective leadership is most associated with use of the political and symbolic frames and with the consistent use of 3 or more frames, this study suggests that program directors would benefit from further leadership development.